MiSo: A DSL for Robust and Efficient Solve and MInimize Problems - Sichetti, Federico; Puppo, Enrico; Huang, Zizhou; Attene, Marco; Zorin, Denis; Panozzo, Daniele (ACM transactions on graphics, 2025)
Many problems in computer graphics can be formulated as finding the global minimum of a function subject to a set of non-linear constraints (Minimize), or finding all solutions of a system of non-linear constraints (Solve). We introduce MiSo, a domain-specific language and compiler for generating efficient C++ code for low-dimensional Minimize and Solve problems, that uses interval methods to guarantee conservative results while using floating point arithmetic. We demonstrate that MiSo-generated code shows competitive performance compared to hand-optimized codes for several computer graphics problems, including high-order collision detection with non-linear trajectories, surface-surface intersection, and geometrical validity checks for finite element simulation.